The bZIP protein from Tamarix hispida, ThbZIP1, is ACGT elements binding factor that enhances abiotic stress signaling in transgenic Arabidopsis - Ji, Xiaoyu (BioMed Central, 2013)
BACKGROUND: Tamarix spp. are woody halophyte, which are very tolerant to abiotic stresses such as salinity and drought, but little is known about their specific stress response systems. Basic leucine zipper proteins (bZIPs) play important roles in the ability of plants to withstand adverse environmental conditions. However, their exact roles in abiotic stress tolerance are still not fully known. In the current study, we functionally characterized a bZIP gene (ThbZIP1) from Tamarix hispida in response to abiotic stresses. RESULTS: We addressed the regulatory network of ThbZIP1 in three levels, i.e. its upstream regulators, the cis-acting elements recognized by ThbZIP1, and its downstream target genes. Two MYCs were found to bind to E-box, in the promoter of ThbZIP1 to activate its expression. Expression of ThbZIP1 is induced by ABA, salt, drought, methyl viologen and cold. ThbZIP1 can specifically bind to ACGT elements, with the highest binding affinity to the C-box, followed by the G-box and lastly the A-box. Compared with wild-type (Col-0) Arabidopsis, transgenic plants expressing ThbZIP1 had an increased tolerance to drought and salt, but had an increased sensitivity to ABA during seed germination and root growth; meanwhile, ROS level, cell death and water loss rate in transgenic plants were significantly reduced. Microarray analyses showed that many ROS scavenging genes were up-regulated by ThbZIP1 under salt stress conditions. CONCLUSIONS: Based on these data, we suggest that ThbZIP1 confers abiotic stress tolerance through activating stress tolerance genes to modulate ROS scavenging ability and other physiological changes involved in stress tolerance, and plays an important role in the ABA-mediated stress response of T. hispida.